Avaliação operando de vacâncias em catalisadores Ni/CeO2 na redução de CO2 - Lucas, Marcela de Andrade [UNESP] (Universidade Estadual Paulista (Unesp), 2025)
The catalytic hydrogenation of CO₂ to CH4 is an effective approach to promote sustainable development, although advancing low-cost and high-performance results still represents a major challenge. Ni/CeO2 catalysts were prepared to investigate how variation in ultrasonic irradiation influences the structure of CeO2, focusing on its structural and catalytic properties in the conversion of CO₂ to CH4. The impact of this variation was analyzed using techniques such as X-ray diffraction (XRD), nitrogen physisorption, scanning electron microscopy (SEM), Rietveld refinement, and Raman spectroscopy. Furthermore, XPS analyses of the Ce3d state were performed to elucidate the structural organization of the surface of these catalysts. The synthesis route showed a system with well-defined pores, with an average diameter of approximately 8 nm. The NiCe0, NiCe1 and NiCe2 samples showed low catalytic activity in the conversion of CO₂ with initial rates of 12%, 15% and 13%, respectively. The selectivity was influenced by exposure to ultrasonic irradiation: an irradiated sample (NiCe0) showed 100% selectivity for CH4, while NiCe1 showed 60% for CO and 40% for CH4 and NiCe2 showed 48% for CO and 51% for CH4. Exposure to higher irradiation significantly improved the catalytic performance, with NiCe4 achieving 43% CO₂ conversion and 100% CH4 selectivity, and NiCe9 achieving 94% conversion, with 3% CO and 96% CH4 selectivity. The correlation between Raman operand data and catalytic evaluations allowed identifying how oxygen vacancies and Ni dispersion directly influence the activity and stability of the materials.

A hidrogenação catalítica de CO₂ em CH4 é uma abordagem eficaz para promover o desenvolvimento sustentável, embora o avanço de resultados de baixo custo e alto desempenho ainda represente um desafio importante. Catalisadores de Ni/CeO2 foram preparados para investigar como a variação ao tempo de exposição na irradiação ultrassônica influencia a estrutura do CeO2, com foco em suas propriedades estruturais e catalíticas na conversão de CO₂ em CH4. O impacto dessa variação foi analisado usando técnicas como difração de raios X (DRX), fisissorção de nitrogênio, microscopia eletrônica de varredura (MEV), refinamento de Rietveld e espectroscopia Raman em condições operando. Além disso, análises XPS do estado Ce3d foram realizadas para elucidar a organização estrutural da superfície desses catalisadores. A rota de síntese mostrou um sistema com poros bem definidos, com diâmetro médio de aproximadamente 8 nm. As amostras NiCe0, NiCe1 e NiCe2 apresentaram baixa atividade catalítica na conversão de CO₂, com taxas iniciais de 12%, 15% e 13%, respectivamente. A seletividade foi influenciada pela exposição a irradiação ultrassônica: uma amostra sem irradiação (NiCe0) apresentou 100% de seletividade para CH4, enquanto NiCe1 apresentou 60% para CO e 40% para CH4 e NiCe2 apresentou 48% para CO e 51% para CH4. A exposição a maior irradiação melhorou significativamente o desempenho catalítico, com NiCe4 alcançando 43% de conversão de CO₂ e 100% de seletividade de CH4, e NiCe9 alcançando 94% de conversão, com 3% de CO e 96% de seletividade de CH4.A correlação entre os dados operando de Raman e as avaliações catalíticas permitiu identificar como as vacâncias de oxigênio e a dispersão do Ni influenciam diretamente a atividade e estabilidade dos materiais.
Operand evaluation of vacancies in Ni/CeO2 catalysts for CO2 reduction
Keywords: Óxidos metálicos; Irradiação ultrassônica; Hidrogenação; Conversão de CO₂; Metal oxides; Ultrasonic irradiation; Hydrogenation; CO₂ conversion